Happy Photometry-Tips and Tricks against the Pitfalls when using a School Photometer - Ehli, Christian (Chemie Konkret - Forum für Unterricht und Didaktik, 2020)
With the help of photometry, a large number of scientific projects can be performed at school. In this context, it is recommended to follow a series of experimental parameters. The following article is a help for identification of possible disruptive factors and troubleshooting.
CRIS-Team WoS Importer:2020-08-07